Investigation of Ultrasonic Flowmeter Error in Distorted Flow Using Two-peak Salami Functions - Fedir Matiko; Vitalii Roman; Halyna Matiko; Dmytro Yalinskyi (Energy Engineering and Control Systems)
Results of investigating the additional error of ultrasonic flowmeters caused by the distortion of the flow are presented in the article. The location coordinates of acoustic paths were calculated for their number from 1 to 6 according to the different numerical integrating methods: Gauss (Gauss-Legendre, Gauss-Jacobi), Chebyshev (equidistant location of acoustic paths), Westinghouse method, method of OWICS (Optimal Weighted Integration for Circular Sections). This made it possible to realize the flowrate equation for multi-path ultrasonic flowmeters and to determine their additional error for different location of the acoustic paths. The average flow velocity along each path is calculated based on the flow velocity profile in the pipe cross section. Four two-peak Salami functions of velocity are used to calculate the velocity profile of the distorted flow caused by typical local resistances. According to the research results the recommendations were developed for choosing the number of the acoustic paths of the ultrasonic flowmeters and for using the methods for determining the location coordinates of the acoustic paths.